(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
During biodegradation, microorganisms can directly metabolize surfactants for energy and nutrients or co-metabolize them with other compounds. Maximum growth of the bacterial consortium on SDS was seen between 30 and 35 °C, while the optimal pH range for bacterial consortium growth was between 6.5 and 7.5. As for the nitrogen source, 2 g/L of ammonium sulfate was optimum in supporting the growth of SDS. The greatest growth rate of the bacterial consortium was recorded at a concentration of between 1 and 1.5 g/L of SDS (p<0.05). At 2–3, g/L of SDS, the bacterial consortium grew more slowly, and at 5 g/L, growth was severely inhibited. Almost complete degradations of SDS were observed in 3, 5 and 6 days at 0.5, 0.75 and 1 g/L SDS, respectively while higher concentrations showed partial degradation with no degradation observed at 2.5 g/L SDS after 6 days of incubation. In this study, the maximum growth rate, or max, Ks, and Ki were 0.517 h-1 (95% confidence interval of C.I. from 0.404 to 0.629), 0.132 (g/L) (95% C.I. from 0.073 to 0.191) and 0.909 (g/L) (95% C.I. from 0.544 to 1.273), respectively. Heavy metals like mercury, copper, and chromium can severely stunt growth if they are present in the environment. It was discovered through research into growth kinetics that Haldane substrate inhibition kinetics may be used to model the growth rate. This bacterial consortium has the right properties for the bioremediation of SDS-polluted environments.